Effects of Estrogen on Histomorphology Steroid-Induced Avascular Necrosis of Head of Femur in Male Rats - Iqbal, Sadaf; Shabnam Hamid; Faiza Umbreen; Mahwash Azam; Ayesha Ali; Maroosh Mirza (Pakistan Armed Forces Medical Journal, 2023)
Objectives: To study the effects of estrogen administration on histomorphology of avascular necrosis of the femoral head in male rats.Study Design: Lab-based experimental study.Place and Duration of Study: Department of Anatomy, Army Medical College, National University of Medical Sciences, Rawalpindi (NUMS), in collaboration with the National Institute of Health Islamabad, (NIH) Pakistan from Aug to Nov 2021.Methodology: Thirty male Sprague Dawley rats, three months of age, weighing 200-300 gm, were selected. Rats were equally divided into three groups. Group-A served as a control group in which no intervention was made, and the rats were fed on a standard lab diet. Groups B and C served as experimental groups. In Groups B and C, avascular necrosis was induced by steroids for the first week of the study. Group C along with steroids also received tab estrogen by oral gavage for eight weeks, starting from the fifth week of the study till the twelfth week of the study. All the rats were sacrificed after the completion of the experimental period. The microscopic parameters like cortical thickness and percentage of the empty lacunae were counted.Results: Histomorphological changes were observed when the comparison was made between Group B, Control Group A, and Experimental Groups B and C with statistically significant results (p-value 0.001).Conclusion: Estrogen helps in fracture healing and shows improvement in cortical and trabecular strength. It has shown improvement in the cortical thickness measurement after avascular necrosis causes a decrease in the thickness.